Applications of Cesàro Submethod to Trigonometric Approximation of Signals (Functions) Belonging to Class Lip(α,p) in Lp-Norm - M. L. Mittal; Mradul Veer Singh (Journal of Mathematics)
We prove two Theorems on approximation of functions belonging to Lipschitz class Lip(α,p) in Lp-norm using Cesàro submethod. Further we discuss few corollaries of our Theorems and compare them with the existing results. We also note that our results give sharper estimates than the estimates in some of the known results.